A Portrait of Trade in Value-Added over Four Decades - Johnson, Robert C.; Noguera, Guillermo (The Review of Economics and Statistics, 2017)
We combine data on trade, production, and input use to document changes in the value-added content of trade between 1970 and 2009. The ratio of value-added to gross exports fell by roughly 10 percentage points worldwide. The ratio declined 20 percentage points in manufacturing, but rose in nonmanufacturing sectors. Declines also differ across countries and trade partners: they are larger for fast-growing countries, for nearby trade partners, and among partners that adopt regional trade agreements. Using a multisector structural gravity model with input-output linkages, we show that changes in trade frictions play a dominant role in explaining all these facts.